Pemberdayaan Masyarakat Dalam Pencegahan Stunting Melalui Sosialisasi, Pemberian Makanan Tambahan dan Peningkatan Kapasitas Kader Posyandu - Misbahuddin; Abdul Kholid; Yunita Sari; Elmy Ericka Stywati; Wira Wawantoro; Baiq Irma Fitriani; Anisaturahman; Suryani Kazrina; Baiq Juliati; Helmi Ilzam Fadholi; Muhammad Amjad Syahrastany (Universitas Mataram, 2022)
Based on WHO’s data in 2013, there are 24.5% of children under five in the world experiencing stunting. Around 80% of stunted children in the world live in 14 countries. Furthermore, based on the results of the 2018 National Basic Health Research, the stunting rate in children in Indonesia reached 30.8%. With West Nusa Tenggara being the area with the 5th highest stunting rate in Indonesia, which is 30.9%. Besides, Ketangga Jeraeng Village is one of the villages that also has the potential for stunting children. The Ketangga Jeraeng village consists of 8 hamlets and 9 Posyandu places. Based on data from the Posyandu in the Ketangan Jeraeng village, there were 1 child identified as stunted and 3 children identified as weight below the red line (WBR). 1 child was identified as stunted from Wates Hamlet. Meanwhile, the 3 WBG children came from the Ketangga Kemalik and Timuk Lauk hamlets. This activity lasts for 45 days starting from June 20 to August 3, 2022, which were conducted by the students of University of Mataram in Community Service Program (CSP). During those 45 days, CSP students in Ketangga Jeraeng Village empowered the community through socialization, Supplementary Food Provision, and capacity building for posyandu cadres. The result of this activity is an increase in knowledge related to how to prevent stunting and how important it is to provide nutritious food for children. In addition, the end result of this activity is also implemented by making nutritious Moringa pudding to prevent stunting. CSP students chose Moringa as the main ingredient in addition to having high nutrition, Moringa is also easy to find in this village so that it will make it easier for mothers to make the product.